A study of the reaction e+e- → μ+μ- around the Z0 pole - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; et al. (1991)
Measurements of the cross section and forward-backward asymmetry for the reaction e+e-→μ+μ- using the DELPHI detector at LEP are presented. The data come from a scan around the Z0 peak at seven centre of mass energies, giving a sample of 3858 events in the polar angle region 22° < θ < 158°. From a fit to the cross section for 43° < θ < 137°, a polar angle region for which the absolute efficiency has been determined, the square root of the product of the Z0→e+e- and Z0→μ+μ- partial widths is determined to be (ΓeΓμ)1/2 = 85.0 ± 0.9 (stat.) ± 0.8 (syst.) MeV. From this measurement of the partial width, the value of the effective weak mixing angle is determined to be sin2(θ̄w) = 0.2267 ± 0.0037. The ratio of the hadronic to muon pair partial widths is found to be Γh/Γμ = 19.89 ± 0.40 (stat.) ± 0.19 (syst.). The forward-backward asymmetry at the resonance peak energy ECMS = 91.22 GeV is found to be AFB = 0.028 ± 0.020 (stat.) ± 0.005 (syst.). From a combined fit to the cross section and forward-backward asymmetry data, the products of the electron and muon vector and axial-vector coupling constants are determined to be VeVμ = 0.0024 ± 0.0015 (stat.) ± 0.0004 (syst.) and AeAμ = 0.253 ± 0.003 (stat.) ± 0.003 (syst.). These results are in good agreement with the expectations of the minimal standard model.